Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1172/jci39354
|View full text |Cite
|
Sign up to set email alerts
|

Potent inhibition of HIV-1 by TRIM5-cyclophilin fusion proteins engineered from human components

Abstract: New World monkeys of the genus Aotus synthesize a fusion protein (AoT5Cyp) containing tripartite motif-containing 5 (TRIM5) and cyclophilin A (CypA) that potently blocks HIV-1 infection. We attempted to generate a human HIV-1 inhibitor modeled after AoT5Cyp, by fusing human CypA to human TRIM5 (hT5Cyp). Of 13 constructs, 3 showed substantial HIV-1-inhibitory activity when expressed in human cell lines. This activity required capsid binding by CypA and correlated with CypA linkage to the TRIM5a capsid-specifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
124
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(133 citation statements)
references
References 68 publications
5
124
0
4
Order By: Relevance
“…Both are predicted to show low immunogenicity when used in vivo. hT5cyp probably has higher potency, 56 certainly not a negligible factor. The single most important determinant for success in vivo, however, is likely to be the emergence (or lack thereof) of HIV-1 variants resistant to the transgenic restriction factor used.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Both are predicted to show low immunogenicity when used in vivo. hT5cyp probably has higher potency, 56 certainly not a negligible factor. The single most important determinant for success in vivo, however, is likely to be the emergence (or lack thereof) of HIV-1 variants resistant to the transgenic restriction factor used.…”
Section: Discussionmentioning
confidence: 97%
“…Our mutant TRIM5a hu antiviral approach begs the comparison with hT5Cyp, 56 the recently constructed TRIMCyp-like restriction factor with very high HIV-1 restriction activity. Both types of gene are likely to inhibit HIV-1 through the same effector mechanisms, although that remains to be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…We also designed a chimera composed of owl monkey TRIM5 effector domains and the inferred parental CypA gene (TRIM5-parentalCypA), representing the CypA gene from which CypA3 derived at the time of its birth. Because CypA genes have been evolving under strong purifying selection throughout primate history, this approach allows us to evaluate the lentiviral specificity of a de novo CypA retrogene unambiguously, representing TRIMCypA3 immediately following its birth (36). Consistent with previous results, we observed that owl monkey TRIMCypA1 was not able to restrict HIV-2 (4) but was able to restrict HIV-1 (15), simian immunodeficiency virus from african green monkeys (SIVagm) (18), and feline immunodeficiency virus (FIV) (37), as well as chimeric viruses encoding the reconstructed capsid of the "paleoviruses" RELIK and pSIV (38) (Fig.…”
Section: Testing Ancient and De Novo Trimcyp Proteins For Restriction Ofmentioning
confidence: 99%
“…RevM10 mutant, the first trans-dominant negative protein to undergo a pilot clinical trial in HIV-1-infected patients (Woffendin et al, 1996;Ranga et al, 1998), was beneficial to cell survival in the context of HIV infection (Podsakoff et al, 2005). A human engineered TRIM5 (tripartite motif 5)-cyclophilin protein introduced into primary CD4 + T cells and macrophages provided extraordinary protection from HIV-1 infection in vitro and in immunecompromised mice (Neagu et al, 2009). TRIM5-cyclophilin inhibits HIV-1 infection in the newly infected cell by binding to capsid protein (CA), leading to downregulated viral reverse transcription.…”
mentioning
confidence: 99%